Ecological Consortium as an Elementary Ecosystem - Anatolij Ivashov; Andriy Simchuk (Vasyl Stefanyk Precarpathian National University, 2022)
Each of the large autotrophic or heterotrophic organisms  reproduces an environment for many organisms, living in, on and around it. This central organism and all other organisms, living in the sphere of its influence, constitute together an elementary community or ecosystem if to take into the consideration soil, air and other elements, which are included into the sphere. In East European ecological tradition such the elementary ecosystems are named individual consortia. Population and species consortia integrate individual consortia of population and species representatives correspondingly. Each central organism has unique genotype, and, thus, reproduces unique environment for its inhabitants. In this reason, the result of interaction between consorters and their host depend both from the   genotype of central organism from one side and from genetic structures of the consorters from another side. Thus, autotrophic or heterotrophic individual consortium is a spatially limited unity of different organisms, zone of life concentration, in which specific composition of living and non-living components with peculiar energetic and informative exchange is forming arround the determinant, anough large central organism.